(untitled) (European Journal of Marketing and Economics, 2018)
Foreign direct investment is an international financial flow that has grown in the last 25-30 years. These financial flows are desirable both from developing countries and developed countries. Although developed countries are those that absorb the largest share of foreign investment, during the last years has increased the share of foreign direct investment directed towards developing countries and countries in transition. Albania has also intensified its efforts to be more competitive in this struggle in attracting these international financial flows. Foreign investment can bring significant benefits to the recipient countries as the effect on economic growth of these countries. These efforts have been efficient in view of the growing trend of foreign direct investment inflows. However, it is necessary to see a broader picture to see if this trend has occurred in the countries of the Western Balkans region as well. The purpose of this paper is to analyze if foreign direct investment impacts the economic growth in Albania. Also this paper analyze whether Albania and the countries of the Western Balkans region have followed the global trend of the FDI flows or not, and to determine the decisive factors in these developments. The methodology of the paper is based on the descriptive analysis of the secondary data collected by the financial institutions in Albania, the region and the world.